Mfsd2a is a transporter for the essential omega-3 fatty acid docosahexaenoic acid - Nguyen, Long N.; Ma, Dongliang; Shui, Guanghou; Wong, Peiyan; Cazenave-Gassiot, Amaury; Zhang, Xiaodong; Wenk, Markus R.; Goh, Eyleen L. K.; Silver, David L. (Nature (London), 2014)
Mfsd2a is the major transporter of the omega-3 fatty acid docosahexaenoic acid (DHA) into brain, with Mfsd2a -knockout mice showing reduced DHA in brain, neuronal cell loss in hippocampus and cerebellum, behavioural disorders and reduced brain size; DHA is transported in a sodium-dependent manner, in the form of lysophosphatidylcholines (LPCs) carrying long-chain fatty acids. Building the blood–brain barrier The blood–brain barrier serves a vital function in maintaining the necessary environment for brain function but is an inconvenient obstacle to brain-directed therapeutics. Two papers published in this issue of Nature report the involvement of Mfsd2a, a member of the major facilitator superfamily regarded previously as an orphan transporter, in two aspects of blood–brain barrier function. David Silver and colleagues identify Mfsd2a as the major transporter for uptake of the omega fatty acid docosahexaenoic acid (DHA) into the brain. Mfsd2a is exclusively expressed in the endothelium of the blood–brain barrier, and Mfsd2a -knockout mice have reduced levels brain DHA, neuronal loss and reduced brain size and function. Chenghua Gu and colleagues find a role for Mfsd2 as a regulator of blood–brain barrier development and function: the barrier becomes 'leaky' in Mfsd2a-deficient mice, possibly a result of increased transcellular vesicular transport. Docosahexaenoic acid (DHA) is an omega-3 fatty acid that is essential for normal brain growth and cognitive function 1 , 2 , 3 , 4 . Consistent with its importance in the brain, DHA is highly enriched in brain phospholipids 5 , 6 , 7 . Despite being an abundant fatty acid in brain phospholipids, DHA cannot be de novo synthesized in brain and must be imported across the blood–brain barrier, but mechanisms for DHA uptake in brain have remained enigmatic. Here we identify a member of the major facilitator superfamily—Mfsd2a (previously an orphan transporter)—as the major transporter for DHA uptake into brain. Mfsd2a is found to be expressed exclusively in endothelium of the blood–brain barrier of micro-vessels. Lipidomic analysis indicates that Mfsd2a -deficient ( Mfsd2a -knockout) mice show markedly reduced levels of DHA in brain accompanied by neuronal cell loss in hippocampus and cerebellum, as well as cognitive deficits and severe anxiety, and microcephaly. Unexpectedly, cell-based studies indicate that Mfsd2a transports DHA in the form of lysophosphatidylcholine (LPC), but not unesterified fatty acid, in a sodium-dependent manner. Notably, Mfsd2a transports common plasma LPCs carrying long-chain fatty acids such LPC oleate and LPC palmitate, but not LPCs with less than a 14-carbon acyl chain. Moreover, we determine that the phosphor-zwitterionic headgroup of LPC is critical for transport. Importantly, Mfsd2a -knockout mice have markedly reduced uptake of labelled LPC DHA, and other LPCs, from plasma into brain, demonstrating that Mfsd2a is required for brain uptake of DHA. Our findings reveal an unexpected essential physiological role of plasma-derived LPCs in brain growth and function.